Pendekatan Metode Lean Six Sigma Untuk Menganalisis Waste Pada Batik Printing Di Puspa Kencana Laweyan - Mutiarahadi, Risti, Hafidh Munawir, S.T., M.Eng, Ida Nursanti, S.T., M.Eng. Sc (2015)
Batik is one of the national cultural heritage that has been internationally recognized. Surakarta city has industrial hub batik one of them is Kampoeng Batik Laweyan. One of the batik industry in Kampoeng Batik is Laweyan Fine Batik Puspa Kencana. On Batik Puspa Kencana producing various types of batik from batik, batik and batik printing. Have good quality and can satisfy the customer / consumer and eliminate waste in the production area is one of the ways that must be done in order to compete in the market one way is to implement lean six sigma approach. The Batik Puspa Kencana there are many different types of waste that are still common. In this study are expected to be obtained waste that occurs in the production area to find the root cause of which will provide input for improvement in the area of ​​production, namely through lean six sigma method. The purpose of this research is knowing what type of waste is in batik printing Puspa Kencana and lowering the highest waste through the proposed improvements in the production of batik printing. From this study, several types of waste that occurs in Batik Puspa Kencana ie waiting time, transportation, process is not appropriate, inventory, defective products and the movement is not necessary. By doing dissemination workshop waste waste obtained defect (defective products) is the highest waste that often occurs in Batik Puspa Kencana. after obtained the highest waste is defect (defective products) and found the missing color defects with the percentage of the most numerous and the second is a defect of fabric stains and therefore in doing repair by using 5R with control. Keywords: Lean Six Sigma, Waste, RCA, 5R